2014
DOI: 10.5195/lesli.2014.12
|View full text |Cite
|
Sign up to set email alerts
|

Prosody and its application to forensic linguistics

Abstract: This article describes three studies in prosody and their potential application to the field of forensic linguistics. It begins with a brief introduction to prosody. It then proceeds to describe Miglio, Gries, & Harris (2014), a comparison of prosodic coding of new information by bilingual Spanish-English speakers and monolingual Spanish speakers. A description of Harris & Gries (2011) follows. This study compares the vowel duration variability of bilingual Spanish-English speakers and monolingual Spanish spea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Their results suggested that if children acquire a language early enough, they are more likely to achieve native-like prosody in both languages, as well as a lack of prosodic transfer from one language to the next. However, Harris et al (2014)) found that adult English-Spanish bilingual speakers (18-25 years of age) displayed a greater use of pitch movement when speaking in Spanish than Spanish monolinguals did, suggesting a prosodic transfer from English to Spanish. Most existing studies agree that BLs use prosody differently than monolinguals do, utilizing features of both of their languages (Gut & Pillai, 2015;Harris et al, 2014).…”
Section: The Use Of Prosody By English Bilingual Speakersmentioning
confidence: 96%
See 1 more Smart Citation
“…Their results suggested that if children acquire a language early enough, they are more likely to achieve native-like prosody in both languages, as well as a lack of prosodic transfer from one language to the next. However, Harris et al (2014)) found that adult English-Spanish bilingual speakers (18-25 years of age) displayed a greater use of pitch movement when speaking in Spanish than Spanish monolinguals did, suggesting a prosodic transfer from English to Spanish. Most existing studies agree that BLs use prosody differently than monolinguals do, utilizing features of both of their languages (Gut & Pillai, 2015;Harris et al, 2014).…”
Section: The Use Of Prosody By English Bilingual Speakersmentioning
confidence: 96%
“…However, Harris et al (2014)) found that adult English-Spanish bilingual speakers (18-25 years of age) displayed a greater use of pitch movement when speaking in Spanish than Spanish monolinguals did, suggesting a prosodic transfer from English to Spanish. Most existing studies agree that BLs use prosody differently than monolinguals do, utilizing features of both of their languages (Gut & Pillai, 2015;Harris et al, 2014). A BL's dominant language is thought to have a stronger influence over the direction of prosodic transfer than their non-dominant language.…”
Section: The Use Of Prosody By English Bilingual Speakersmentioning
confidence: 96%
“…Several past studies were conducted on cases of semantic prosody with sample words such as happen, set in, naked eye, build up (Louw, 1993); cause and happen (Bublitz, 1996); and break out (Stubbs, 1995). These studies pointed out that the use of SP in context may reveal the mental or emotional state of a user (Harris et al, 2014). Sinclair (1991) adds to this stating that the user's mental and unconscious state works upon an idiom principle, meaning that it is based on multi-word combinations and the connotational features of the lexical items.…”
Section: Reviewmentioning
confidence: 99%
“…Decisions regarding which speech recordings to select and their sequence have the potential to influence witnesses and interpretations of evidence. Some examples that have been studied include accent [7] and prosody [8]. With respect to presenting materials and findings at judiciary proceedings, it is of upmost importance to eliminate or minimise any biasing features.…”
Section: Introductionmentioning
confidence: 99%